Protease production from Jatropha curcas using Aspergillus niger - Nurul Iwani, Alawi; Khairul Farihan, Kasim; Mohamed Zulkali, Mohamed Daud, Prof, Madya Dr. (University Malaysia Perlis (UniMAP), 2011)
Malaysian International Conference on Trends in Bioprocess Engineering (MICOTriBE) 2009 organized by Univesiti Malaysia Perlis (UniMAP), 12th - 13th December 2009 at Putra World Trade Center (PWTC), Kuala Lumpur, Malaysia.